2019
DOI: 10.4081/aamr.2019.82
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal care uptake and associated factors among nursing mothers in Benin City, Edo State, Nigeria

Abstract: Globally, postnatal care is a strategic public health intervention to aid significant reduction in maternal and neonatal morbidity and mortality especially in developing countries. This study aimed to assess the level of postnatal care (PNC) uptake and associated factors among nursing mothers for improved maternal and newborn outcomes in Benin City, Edo State. Two hundred and twenty (220) nursing mothers attending immunization clinics in University of Benin Teaching hospital, Benin City were studied using a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…Globally, attitude toward PNC is generally good as studies in Ethiopia, Tanzania, and Nigeria have shown. [9][10][11] This corroborates respondents' attitude to PNC in this study which was generally good as the majority of respondents in both the urban and rural communities (93.8% and 76.2%, respectively) had a positive attitude. This is also similar to a study done in Lagos where mothers were found to have a very good attitude toward a component of PNC.…”
Section: Discussionsupporting
confidence: 83%
“…Globally, attitude toward PNC is generally good as studies in Ethiopia, Tanzania, and Nigeria have shown. [9][10][11] This corroborates respondents' attitude to PNC in this study which was generally good as the majority of respondents in both the urban and rural communities (93.8% and 76.2%, respectively) had a positive attitude. This is also similar to a study done in Lagos where mothers were found to have a very good attitude toward a component of PNC.…”
Section: Discussionsupporting
confidence: 83%
“…Occupational exposure to sharp injuries are associated with transmission of potentially infectious pathogens, such Human immunodeficiency virus, Hepatitis B and C virus [1,3]. This has continue to pose threats to healthcare workers at all level of health care.…”
Section: Discussionmentioning
confidence: 99%
“…Exposures are probably overlooked by the HCWs because of false negative results obtained during window period of the viral infection. 3 Therefore, the aftermath of not reporting or utilizing PEP as stipulated by CDC, may result in an unseen increase of occupationally acquired viral infections [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations